Pengaruh Media Sosial, Literasi Ekonomi, dan Kelompok Teman Sebaya Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi - Firyal Naufali Muttaqin; Leny Noviani; Sudarno Sudarno (Jurnal Pendidikan Ekonomi (JUPE), 2022)
The progression of time, combined with technological advancements, has resulted in changes in practically every aspect of existence. Changes in community consumption patterns, particularly among students, are included. Today's students' consumption is driven by personal interests rather than essential necessity. This consumption pattern is influenced by a variety of circumstances. This study aims to determine how the relationship between social media, economic literacy and the environment of students' peers in influencing the consumptive behavior of Economic Education students at Sebelas Maret University, class of 2017-2019. Sampling in this study used a proportionate stratified random sampling technique with 155 students as samples. This study uses quantitative methods with data analysis using t-test and multiple linear regression. The findings of this study show that the factors of social media, economic literacy, and groups of friends of the same age have a positive and significant influence on consumption behavior in economic education students class 2017-2019, with a value of Fcount > Ftable of 18.745 > 2.66.